A gel plaster of external nonsteroidal anti-inflammatory drugs and preparation method thereof

By using carboxymethylcellulose to graft acrylic-acrylamide and polyacrylic-polysiloxane framework materials, the problem of inadequate adhesion of gel paste paste is solved, and softness and adhesion are achieved A highly reproducible gel paste improves the transdermal penetration and stability of the drug.

CN118161467BActive Publication Date: 2024-12-24HANGZHOU HONGYOU PHARM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410243466.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2024-12-24
Estimated Expiration
2044-03-04

AI Technical Summary

Technical Problem

During the use of gel paste, the paste is prone to leaking through the paste, which leads to inconvenient use and the problem of degradation of hardness and adhesion caused by inorganic fillers.

Method used

Carboxymethylcellulose grafted acrylic-acrylamide as a filler, combined with polyacrylic-polysiloxane skeleton material, the moldability and adhesion of the gel paste are improved through crosslinking reaction to avoid the paste being penetrated.

Benefits of technology

The softness, adhesion and reproducibility of gel paste are achieved, the paste penetration is avoided, and the transdermal penetration and stability of the drug are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004725141970000051
    Figure BDA0004725141970000051
  • Figure BDA0004725141970000061
    Figure BDA0004725141970000061
  • Figure BDA0004725141970000071
    Figure BDA0004725141970000071
Patent Text Reader

Abstract

The present application discloses a gel plaster of an external nonsteroidal anti-inflammatory drug and a preparation method thereof. The gel plaster of an external nonsteroidal anti-inflammatory drug comprises a backing layer, a paste layer and an anti-sticking layer, wherein the paste layer comprises the following raw materials in mass fractions: 0.3-5% of active ingredient, 3-15% of skeleton material, 0.5-10% of filler, 0.03-1% of cross-linking agent, 0.05-5% of cross-linking regulator, 5-20% of moisturizer, 0.2-5% of penetration enhancer, 0.5-5% of viscosity enhancer, 0.2-2% of pH regulator and the balance of purified water, and the filler is carboxymethyl cellulose grafted with acrylic acid-acrylamide, which has strong water absorption and water retention properties, gives the gel plaster softness and formability, and can also form an interaction force with the skeleton material to increase the cross-linking density in the system, thereby avoiding the problem of paste seepage during use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of gel patches, and in particular to a gel patch of an external non-steroidal anti-inflammatory drug and a preparation method thereof. Background Art

[0002] Nonsteroidal anti-inflammatory drugs have good antipyretic, analgesic and anti-inflammatory effects, and are widely used in the treatment of rheumatic diseases, rheumatoid diseases, inflammatory diseases, pain, soft tissue and sports injuries. With the widespread clinical application of nonsteroidal anti-inflammatory drugs, their side effects are becoming increasingly apparent. The main adverse reactions include gastrointestinal ulcers, bleeding, liver and kidney damage, cardiovascular damage, etc.

[0003] The gel patch is a patch made by mixing the drug with a suitable hydrophilic matrix and then coating it on a backing material. It has the advantages of good skin compatibility, large drug loading capacity, ability to promote drug penetration through the skin stratum corneum, and ease of use. Combining non-steroidal anti-inflammatory agents with gel patches can avoid problems such as first-pass effect in the liver, gastrointestinal inactivation, and digestive tract discomfort through transdermal absorption, and can maintain constant blood drug concentrations and pharmacological effects, reducing adverse drug reactions.

[0004] In the preparation process of gel patches, inorganic fillers such as kaolin, diatomaceous earth, calcium carbonate, silicon dioxide, etc. are usually used as filling media, so that the obtained gel patches have a certain degree of formability, but it also causes the paste layer of the gel patches to be hard or the viscosity to decrease. Compared with inorganic fillers, water-retaining resins not only have good water absorption and water retention, which can give the gel patches a certain degree of formability, but also make the obtained gel patches soft. However, with the addition of water-retaining resins, when there is excessive water in the system, the paste will seep into the cloth during the application process, which brings inconvenience to use. Summary of the invention

[0005] In order to solve the problem of paste seepage that may occur in gel patches and obtain a gel patch with soft paste, strong adhesion and good cross-linking performance, the present application provides a gel patch of external non-steroidal anti-inflammatory drugs and a preparation method thereof.

[0006] In a first aspect, the present application provides a gel patch of an external non-steroidal anti-inflammatory drug, comprising a backing layer, a paste layer and an anti-adhesive layer, wherein the paste layer comprises the following raw materials in mass fractions:

[0007] Active ingredient 0.3-5%;

[0008] Framework material 3-15%;

[0009] Filler 0.5-10%;

[0010] Cross-linking agent 0.03-1%;

[0011] Cross-linking regulator 0.05-5%;

[0012] Moisturizer 5-20%;

[0013] Penetration enhancer 0.2-5%;

[0014] Thickener 0.5-5%;

[0015] pH regulator 0.2-2%;

[0016] Purified water balance;

[0017] The filler is carboxymethyl cellulose grafted with acrylic acid-acrylamide.

[0018] Preferably, the backing layer is one of artificial cotton cloth and non-woven fabric.

[0019] Preferably, the anti-sticking layer is one of polypropylene film, polyethylene film, anti-sticking paper, and hard gauze.

[0020] Preferably, the active ingredient includes one or a combination of diclofenac, ibuprofen, ketoprofen, flurbiprofen, indomethacin, piroxicam, and loxoprofen.

[0021] Since inorganic fillers can make the gel patch paste harder and reduce its adhesion, and since inorganic fillers may lead to product non-reproducibility due to being produced in different places, by adopting the above-mentioned technical scheme, using a water-retaining resin, i.e., carboxymethyl cellulose grafted with acrylic acid-acrylamide to replace the inorganic filler, it is possible to maintain the formability of the gel patch while also maintaining the softness, adhesion and reproducibility of the gel patch.

[0022] Specifically, carboxymethyl cellulose is a raw material for synthesizing highly absorbent resins, has strong water absorption and water retention properties, and also has certain biocompatibility, can replace inorganic fillers, store medium water in systems with high water content, and maintain the softness of gel patches. The carboxymethyl cellulose in this application is grafted with polyacrylic acid and polyacrylamide, which prolongs the molecular chain of carboxymethyl cellulose, increases the content of polar groups in carboxymethyl cellulose, and thus increases the water retention capacity of carboxymethyl cellulose. At the same time, the grafted modified carboxymethyl cellulose can also form an interaction force with the skeleton material in the system, further increasing the cross-linking density in the system, increasing the formability of the gel patch, and will not cause the problem of paste seepage during use. In addition, the addition of grafted polymers such as polyacrylic acid and polyacrylamide can provide more polar groups than general inorganic fillers, thereby increasing the adhesion of the gel patch.

[0023] Preferably, the raw materials for the carboxymethyl cellulose grafted with acrylic acid-acrylamide include carboxymethyl cellulose, acrylic acid and acrylamide in a mass ratio of 1:(3-4):(3-4).

[0024] By adopting the above technical scheme, a large number of hydroxyl groups are contained in carboxymethyl cellulose, which can react and connect with the carboxyl groups and amide groups contained in acrylic acid and acrylamide, and acrylic acid and acrylamide can undergo polymerization reaction under the action of an initiator. Furthermore, polyacrylic acid and polyacrylamide can be grafted on the surface of carboxymethyl cellulose. The water retention performance of carboxymethyl cellulose after grafting modification is significantly improved, and the content of polar groups of carboxymethyl cellulose is also greatly increased, thereby further improving the crosslinking performance and adhesion of the gel patch.

[0025] Preferably, the carboxymethyl cellulose grafted with acrylic acid-acrylamide is prepared according to the following method:

[0026] In a nitrogen atmosphere, carboxymethyl cellulose is added to distilled water, the temperature is increased to 50-60°C, and the carboxymethyl cellulose aqueous solution is obtained by stirring and dissolving; a neutralizer is added to acrylic acid, the pH value is adjusted to 6.5-7, and then the neutralized acrylic acid, acrylamide and a cross-linking agent are added to the carboxymethyl cellulose aqueous solution, and the mixture is stirred and mixed for 10-15 minutes, and then an initiator is added, the temperature is increased to 40-45°C, and the reaction is stirred for 3-3.5 hours, and then the carboxymethyl cellulose grafted with acrylic acid-acrylamide is obtained through washing and drying.

[0027] Preferably, the cross-linking agent is N,N-methylenebisacrylamide, and the mass ratio of the cross-linking agent to carboxymethyl cellulose is (0.006-0.008):1; the initiator is one or a combination of ammonium persulfate and ammonium bisulfite, and the mass ratio of the initiator to carboxymethyl cellulose is (0.06-0.15):1.

[0028] Preferably, the neutralizing agent is a sodium hydroxide aqueous solution with a mass fraction of 2%.

[0029] By adopting the above technical scheme, under the action of a cross-linking agent, acrylic acid monomers and acrylic acid amide monomers can react and connect with carboxymethyl cellulose. Further, under the action of an initiator, the monomers are polymerized, and polyacrylic acid and polyacrylamide are grafted on the surface of the carboxymethyl cellulose. Polyacrylic acid and polyacrylamide can form intermolecular forces with polar groups contained in the skeleton material, thereby enhancing the binding force between the filler and the skeleton material, improving the dispersibility of the filler in the system, and preventing agglomeration from occurring. The cross-linking density of the system is increased, and the mechanical properties and adhesion performance of the gel patch are enhanced.

[0030] Preferably, the skeleton material is polyacrylic acid-polysiloxane; the raw materials of the polyacrylic acid-polysiloxane include acrylic acid and methacryloyloxypropyl cage-type polysilsesquioxane in a mass ratio of 1: (0.04-0.07).

[0031] By adopting the above technical solution, in order to compensate for the problem that the strength of the water-retaining resin is not as good as that of the inorganic filler, a skeleton material polyacrylic acid-polysiloxane is also added in the present application. The introduction of the skeleton material can improve the formability of the gel patch together with the filler, increase the crosslinking density in the system, and improve the mechanical properties of the system.

[0032] Specifically, polyacrylic acid has strong adhesion, which can increase the adhesion of the gel patch, and the polar groups contained in it can form a reaction cross-link with the polar groups contained in the filler, further improving the formability and cross-linking performance of the gel patch. However, the skeleton material formed by polyacrylic acid alone has poor air permeability and insufficient toughness, so methacryloyloxypropyl cage-type polysilsesquioxane is added to the polyacrylic acid to modify it.

[0033] Methacryloyloxypropyl cage-type polysilsesquioxane has a very stable chemical structure, in which the eight vertices are connected with variable groups, which have good reactivity. Polyacrylic acid reacts and connects with the active groups at the vertices, gradually forming a cross-linked network structure, in which the pores can accommodate active ingredients and protect them from the influence of the external environment. At the same time, polyacrylic acid, as a skeleton material, can also promote the release of active ingredients, increase the transdermal permeability of the gel patch, and stabilize the performance of the gel patch. In addition, the cross-linked network structure formed by polyacrylic acid and methacryloyloxypropyl cage-type polysilsesquioxane can enhance the cross-linking performance of the system, and the phenomenon of paste penetration is not easy to occur.

[0034] Preferably, the polyacrylic acid-polysiloxane is prepared according to the following method:

[0035] Azobisisobutyronitrile and methacryloyloxypropyl cage-type polysilsesquioxane are added to a solvent, and acrylic acid is added after mixing. In a nitrogen atmosphere, the temperature is increased to 60-65° C., and the mixture is stirred for reaction for 5-6 hours, and then washed and dried to obtain polyacrylic acid-polysiloxane.

[0036] By adopting the above technical scheme, azobisisobutyronitrile is used as an initiator to initiate copolymerization of acrylic acid monomers on the active groups at the top corners of methacryloyloxypropyl cage-type polysilsesquioxane, gradually forming a molecular structure of a cross-linked network, which can not only make up for the problem of insufficient mechanical properties of water-retaining resins, but also form a reaction link with carboxymethyl cellulose grafted acrylic acid-acrylamide, promote the combination between components in the system, improve the cross-linking performance of the gel patch, avoid the occurrence of paste seepage, and the polar groups contained can further improve the adhesion of the gel patch. At the same time, the cross-linked network structure formed by the skeleton material in the gel patch can protect the active ingredients in the gel patch, and is not easily inactivated by the external environment, and finally obtains a gel patch with excellent performance, soft texture and good adhesion.

[0037] Preferably, the penetration enhancer includes one or a combination of laurocapram, menthol, isopropyl myristate, peppermint oil, oleic acid, propylene glycol, and polyethylene glycol.

[0038] By adopting the above technical scheme, the penetration enhancer selected in the present application meets the biocompatibility requirements and minimizes the damage of the penetration enhancer itself to the human body. It can promote the penetration of drugs into the skin and reduce the resistance encountered by drugs when passing through the skin, further promoting the active ingredients in the gel patch to pass through the stratum corneum and diffuse into the epidermis.

[0039] Preferably, the cross-linking agent includes one or a combination of aluminum hydroxide, aluminum glycolate, aluminum trichloride, aluminum sulfate, composite aluminum salt, aluminum chloride, potassium aluminum sulfate, aluminum citrate, and magnesium aluminosilicate;

[0040] The cross-linking regulator includes one or a combination of tartaric acid, citric acid, malic acid, edetic acid and sodium salts thereof;

[0041] The moisturizer includes one or a combination of glycerin, propylene glycol, sorbitol, and polyethylene glycol;

[0042] The viscosity enhancer includes one or a combination of gelatin, gum arabic, tragacanth gum, peach gum, xanthan gum, and guar gum; the pH adjuster includes one or a combination of L-tartaric acid, DL-tartaric acid, phosphoric acid, citric acid, and malic acid.

[0043] Preferably, the filler and skeleton material in the system can chemically react with the metal ions contained in the cross-linking agent to form a cross-linked three-dimensional structure, thereby improving the strength and stability of the gel patch, while the cross-linking regulator can catalytically regulate the cross-linking speed and degree to prevent the gel patch from having too low a cross-linking density or excessive cross-linking during the preparation process.

[0044] In a second aspect, the present application also provides a method for preparing a gel plaster of an external non-steroidal anti-inflammatory drug, comprising the following steps:

[0045] S1. The active ingredient, the penetration enhancer and the viscosity enhancer are mixed to obtain a first mixed solution;

[0046] S2. The filler and the skeleton material are mixed and added to purified water, and stirred to obtain a second mixed solution;

[0047] S3. The cross-linking agent, the cross-linking regulator and the pH regulator are added to the humectant, and the mixture is stirred and dispersed to obtain a third mixed solution;

[0048] S4. The first mixed liquid, the second mixed liquid and the third mixed liquid are stirred and mixed to form a uniform white paste, which is then coated on the backing layer, covered with an anti-adhesive layer and pressed, and finally cut to obtain a gel patch of external non-steroidal anti-inflammatory drugs.

[0049] In summary, this application has the following beneficial effects:

[0050] 1. In the gel patch of the present application, carboxymethyl cellulose grafted with acrylic acid-acrylamide is used to replace inorganic fillers. Carboxymethyl cellulose grafted with acrylic acid-acrylamide has strong water absorption and water retention properties, stores medium water in a system with a large water content and maintains the softness of the gel patch. The grafted copolymer extends the molecular chain of carboxymethyl cellulose and increases the content of polar groups in the carboxymethyl cellulose, thereby improving adhesion. At the same time, it can also form an interaction force with the skeleton material in the system, further increasing the cross-linking density in the system, increasing the formability of the gel patch while preventing the problem of paste seepage during use.

[0051] 2. The present application also adds a skeleton material polyacrylic acid-polysiloxane. The introduction of the skeleton material can improve the formability of the gel patch together with the filler, increase the cross-linking density in the system, and improve the transdermal permeability of the active ingredient. The cross-linked network structure formed by polyacrylic acid and methacryloxypropyl cage-type polysilsesquioxane can enhance the cross-linking performance of the system, and the paste is not prone to seepage. DETAILED DESCRIPTION

[0052] Preparation Example of Carboxymethyl Cellulose Grafted with Acrylic Acid-Acrylamide

[0053] Preparation Example 1-1, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, is prepared according to the following method:

[0054] Under nitrogen atmosphere, 10 g of carboxymethyl cellulose (viscosity 2500-4500 mPa.s) was added to 250 ml of distilled water, the temperature was raised to 60° C., and the solution was stirred to obtain a carboxymethyl cellulose aqueous solution.

[0055] A 2% sodium hydroxide solution was added to 30 g of acrylic acid to adjust the pH value of the acrylic acid to 7, and then the neutralized acrylic acid, 40 g of acrylamide and 0.07 g of N,N-methylenebisacrylamide were added to the carboxymethyl cellulose aqueous solution, stirred and mixed for 15 minutes, and then 1 g of initiator (wherein the initiator is a mixture of ammonium persulfate and ammonium bisulfite in a mass ratio of 1:1) was added, the temperature was increased to 45° C., the reaction was stirred for 3 hours, and then the carboxymethyl cellulose grafted with acrylic acid-acrylamide was obtained after washing and drying.

[0056] Preparation Example 1-2 to Preparation Example 1-7, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, differs from Preparation Example 1-1 only in that the ratio of raw materials in the preparation process is different, as shown in Table 1:

[0057] Table 1 Formulations of Preparation Examples 1-1 to 1-7

[0058]

[0059]

[0060] The mass ratio of ammonium persulfate to ammonium bisulfite in Preparation Examples 1-1 to 1-7 is 1:1.

[0061] Preparation Example 1-8, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, is different from Preparation Example 1-1 only in that the amount of acrylic acid added is 25 g.

[0062] Preparation Example 1-9, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, is different from Preparation Example 1-1 only in that the amount of acrylic acid added is 45 g.

[0063] Preparation Example 1-10, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, is prepared according to the following method: under a nitrogen atmosphere, 10g of carboxymethyl cellulose (viscosity of 2500-4500mPa.s) is added to 250ml of distilled water, the temperature is raised to 60°C, and the carboxymethyl cellulose aqueous solution is obtained by stirring and dissolving. 70g of acrylamide and 0.07g of N,N-methylenebisacrylamide are added to the carboxymethyl cellulose aqueous solution, stirred and mixed for 15 minutes, and 1g of initiator (wherein the initiator is a mixture of ammonium persulfate and ammonium bisulfite in a mass ratio of 1:1) is added, the temperature is raised to 45°C, stirred and reacted for 3h, and then washed and dried to obtain carboxymethyl cellulose grafted with acrylic acid-acrylamide.

[0064] Preparation Example 1-11, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, is different from Preparation Example 1-1 only in that the added amount of N,N-methylenebisacrylamide is 0.05 g.

[0065] Preparation Example 1-12, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, is different from Preparation Example 1-1 only in that the added amount of N,N-methylenebisacrylamide is 0.09 g.

[0066] Preparation Example 1-13, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, is different from Preparation Example 1-1 only in that the amount of initiator added is 0.5 g.

[0067] Preparation Example 1-14, a carboxymethyl cellulose grafted with acrylic acid-acrylamide, is different from Preparation Example 1-1 only in that the amount of initiator added is 1.6 g.

[0068] Preparation Example of Polyacrylic Acid-Polysiloxane

[0069] Preparation Example 2-1, a polyacrylic acid-polysiloxane, was prepared according to the following method:

[0070] 0.2 g of azobisisobutyronitrile and 0.6 g of methacryloyloxypropyl cage-type polysilsesquioxane were added to the dried tetrahydrofuran, and 10 g of acrylic acid was added after stirring and mixing. The temperature was raised to 60° C. under a nitrogen atmosphere, and the mixture was stirred for reaction for 5.5 h, and then washed and dried to obtain polyacrylic acid-polysiloxane.

[0071] Preparation Example 2-2, a polyacrylic acid-polysiloxane, is different from Preparation Example 2-1 only in that the added amount of methacryloxypropyl cage-type polysilsesquioxane is 0.4 g.

[0072] Preparation Example 2-3, a polyacrylic acid-polysiloxane, is different from Preparation 2-1 only in that the added amount of methacryloxypropyl cage-type polysilsesquioxane is 0.7 g.

[0073] Example

[0074] Example 1, a gel plaster of a topical nonsteroidal anti-inflammatory drug, is prepared according to the following method:

[0075] S1. 3 g of loxoprofen, 3 g of gelatin and 2 g of isopropyl myristate were mixed to obtain a first mixed solution;

[0076] S2. 6 g of carboxymethyl cellulose grafted with acrylic acid - acrylic acid prepared in Preparation Example 1-1 and 10 g of polyacrylic acid - polysiloxane prepared in Preparation Example 2-1 were mixed and added to 60.2 g of purified water, and stirred to obtain a second mixed solution;

[0077] S3. 0.5 g of aluminum hydroxide, 2.5 g of edetic acid and 0.8 g of citric acid were added to 12 g of glycerol and stirred to obtain a third mixed solution;

[0078] S4. The first mixed liquid, the second mixed liquid and the third mixed liquid are stirred and mixed to form a uniform white paste, and then coated on a backing layer (non-woven fabric is selected as the backing layer), and then covered with an anti-sticking layer (polyethylene film is selected as the anti-sticking layer) for pressing, and finally cut to obtain a gel patch of external non-steroidal anti-inflammatory drugs.

[0079] Examples 2 to 11 are gel patches of external nonsteroidal anti-inflammatory drugs, which differ from Example 1 only in that the ratios of the raw materials used are different, as shown in Table 2:

[0080] Table 2 Formulations of Examples 1 to 11

[0081]

[0082]

[0083] The materials used are the carboxymethyl cellulose grafted with acrylic acid-acrylamide prepared in Preparation Example 1-1 and the polyacrylic acid-polysiloxane prepared in Preparation Example 2-1.

[0084] Example 12, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-2.

[0085] Example 13, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-3.

[0086] Example 14, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-4.

[0087] Example 15, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-5.

[0088] Example 16, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-6.

[0089] Example 17, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-7.

[0090] Example 18, a gel patch of an external nonsteroidal anti-inflammatory drug, is different from Example 1 only in that an equal amount of polyacrylic acid-polysiloxane prepared in Preparation Example 2-2 is used to replace the polyacrylic acid-polysiloxane prepared in Preparation Example 2-1.

[0091] Example 19, a gel patch of an external nonsteroidal anti-inflammatory drug, is different from Example 1 only in that an equal amount of polyacrylic acid-polysiloxane prepared in Preparation Example 2-3 is used to replace the polyacrylic acid-polysiloxane prepared in Preparation Example 2-1.

[0092] Example 20, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-8.

[0093] Example 21, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-9.

[0094] Example 22, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-11.

[0095] Example 23, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-12.

[0096] Example 24, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-13.

[0097] Example 25, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-14 is used to replace the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1.

[0098] Comparative Example

[0099] Comparative Example 1, a gel patch of an external nonsteroidal anti-inflammatory drug, is different from Example 1 only in that the added amount of the polyacrylic acid-polysiloxane prepared in Preparation Example 2-1 is 2 g.

[0100] Comparative Example 2, a gel patch of an external nonsteroidal anti-inflammatory drug, is different from Example 1 only in that the amount of polyacrylic acid-polysiloxane prepared in Preparation Example 2-1 added is 16 g.

[0101] Comparative Example 3 is a gel patch for external use of nonsteroidal anti-inflammatory drugs, which is different from Example 1 only in that the polyacrylic acid-polysiloxane prepared in Preparation Example 2-1 is not added.

[0102] Comparative Example 4 is a gel patch for external use of nonsteroidal anti-inflammatory drugs, which is different from Example 1 only in that the added amount of carboxymethyl cellulose grafted with acrylic acid-acrylamide prepared in Preparation Example 1-1 is 0.3 g.

[0103] Comparative Example 5, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the added amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is 12 g.

[0104] Comparative Example 6, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1 is replaced by an equal amount of carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-10.

[0105] Comparative Example 7, a gel patch for external use of nonsteroidal anti-inflammatory drugs, is different from Example 1 only in that an equal amount of kaolin (200 mesh kaolin) is used to replace the carboxymethyl cellulose grafted acrylic acid-acrylamide prepared in Preparation Example 1-1.

[0106] Performance testing

[0107] 1. Adhesion test: According to the relevant provisions of "0952 Adhesion Determination Method" in Part IV of the 2020 edition of the Chinese Pharmacopoeia, the initial adhesion and adhesion of the obtained gel patch were tested. The initial adhesion was determined by the first method (determination of initial adhesion) using the rolling ball slope stop method; the adhesion was determined by the fourth method (determination of adhesion). The experimental results are shown in Table 3.

[0108] 2. In vitro skin permeation test: Follow the following test steps:

[0109] After the diffusion cell is installed, add an appropriate amount of medium (specifically a phosphate buffer solution with a pH value of 7.4) to the diffusion cell, which is about 2 / 3 of the volume of the diffusion cell. Set the speed and temperature. After the temperature is constant (specifically 32°C), take the prepared gel patch, remove the anti-stick layer, and stick it to the middle of the pig skin (25 mm in diameter). Spread the pig skin on the diffusion cell so that the pig skin is aligned with the center of the diffusion cell, put on the sealing gasket and jacket, tighten the screws, and fix the diffusion cell, pig skin, sealing gasket and jacket. The test preparation and the reference preparation are alternately placed. Supplement excess receiving medium to fill the diffusion cell, so that the pig skin is in complete contact with the receiving medium liquid surface (no bubbles are allowed), the medium should fill the diffusion cell, and the excess release medium should be discharged from the drain pipe. At the beginning of the experiment, samples were taken for testing at 6h, 12h, and 24h.

[0110] The test results are shown in Table 4.

[0111] Table 3 Gel patch adhesion test results

[0112]

[0113]

[0114] Table 4 Results of transdermal test of gel patch

[0115]

[0116] According to Table 3 and Table 4, combined with Example 1, Example 2 to Example 11, it can be seen that the initial adhesion, adhesion and average cumulative permeability of the gel patch obtained in Example 2 to Example 11 are not much different from those in Example 1, indicating that the adhesion performance and transdermal properties of Example 2 to Example 11 are not much different from those in Example 1. The reason may be that the difference between Example 2 to Example 11 and Example 1 is only that the raw materials used in Example 2 to Example 11 are changed within the required range, indicating that changing the ratio of raw materials within the required range has little effect on the performance of the obtained gel patch.

[0117] Combining Example 1 and Examples 12 to 19, it can be seen that the initial adhesion, adhesion and average cumulative permeability of the gel patch obtained in Examples 12 to 19 are not much different from those in Example 1, indicating that the adhesion performance and transdermal properties of Examples 12 to 19 are not much different from those in Example 1. The reason may be that the difference between Examples 12 to 19 and Example 1 is only that the fillers and skeleton materials used in Examples 12 to 19, i.e., carboxymethyl cellulose grafted acrylic acid-acrylamide and polyacrylic acid-polysiloxane, are changed in the required range during the preparation process, indicating that changing the ratio of the filler and skeleton material raw materials within the required range has little effect on the performance of the obtained gel patch.

[0118] Combining Example 1 and Examples 20 to 25, it can be seen that the initial adhesion, adhesion and average cumulative permeability of the gel patches obtained in Examples 20 to 25 are lower than those in Example 1, indicating that the adhesion performance and transdermal properties of Examples 20 to 25 are lower than those in Example 1. The reason may be that the difference between Examples 20 to 25 and Example 1 is that the ratio of raw materials added to the filler, i.e., carboxymethyl cellulose grafted with acrylic acid-acrylamide, used in Examples 20 to 25 during the preparation process has been changed. Specifically, the amount of acrylic acid added in Examples 20 and 21 has been changed. The reduction in the content of acrylic acid will lead to a decrease in the number of polar groups contained in the carboxymethyl cellulose grafted with acrylic acid-acrylamide, thereby causing the crosslinking performance of the gel patch to decrease and the adhesion to decrease. When the content of acrylic acid increases, the carboxymethyl cellulose can no longer provide more grafting points, and the acrylic acid monomer undergoes homopolymerization, resulting in a decrease in the grafting rate of the carboxymethyl cellulose, thereby reducing the crosslinking performance of the gel patch; the amount of crosslinking agent added in Examples 22 and 23 has been changed. In Example 22, the amount of cross-linking agent added is reduced, the degree of cross-linking is low, the grafting rate decreases accordingly, and the cross-linking performance of the gel patch also decreases accordingly. In Example 23, the amount of cross-linking agent added is increased, the degree of cross-linking is too high, and the three-dimensional structure formed by it will affect the grafting reaction between acrylic acid monomer and acrylamide monomer and carboxymethyl cellulose during the preparation process, thereby causing a decrease in the grafting rate; the amount of initiator added in Example 24 and Example 25 is changed. In Example 24, the amount of initiator added is reduced, the rate of free radicals generated by the decomposition of the initiator is low, the grafting points are reduced, and many monomers fail to participate in the reaction. In Example 25, the amount of initiator added is increased, and during the preparation process, the free radicals in the system increase. In the process of initiating monomer polymerization, it will cause explosion, thereby affecting the grafting rate of carboxymethyl cellulose, and thus the performance of the gel patch is affected.

[0119] Combining Example 1 and Comparative Examples 1 to 3, it can be seen that the initial adhesion, adhesion and average cumulative permeability of the gel patches obtained in Comparative Examples 1 to 3 are lower than those in Example 1, among which Comparative Examples 1 and 3 are significantly reduced, indicating that the adhesion performance and transdermal properties of Comparative Examples 1 to 3 are lower than those in Example 1. The reason may be that, compared with Example 1, in the preparation process of the gel patch, the addition amount of the skeleton material in Comparative Examples 1 to Comparative Examples 3 was adjusted. Among them, the addition amount of the skeleton material was reduced in Comparative Example 1. On the one hand, it was unable to form a mutual binding force with the carboxymethyl cellulose grafted acrylic acid-acrylamide in the system to make up for the problem of insufficient filler strength. The content of polar groups also decreased, and the adhesion of the system decreased. On the other hand, the content of the skeleton material was reduced, the protection of the active ingredients in the system was weakened, and the transdermal permeability of the gel patch decreased. In Comparative Example 3, no skeleton material was added, and the performance of the gel patch decreased more significantly. In Comparative Example 2, the addition amount of the skeleton material was increased, which would lead to an increase in the cross-linking strength of the overall system. Due to excessive cross-linking, the active ingredients in the gel patch were difficult to penetrate and penetrate into the human body, thereby resulting in a decrease in the adhesion and permeability of the gel patch.

[0120] Combining Example 1, Comparative Example 4 and Comparative Example 5, it can be seen that the initial adhesion, adhesion and average cumulative permeability of the gel patch obtained in Comparative Example 4 and Comparative Example 5 are lower than those in Example 1, and the decrease in Comparative Example 4 is obvious, indicating that the adhesion performance and transdermal properties of Comparative Example 4 and Comparative Example 5 are lower than those in Example 1. The reason may be that in the preparation process of the gel patch, the amount of the filler, i.e., carboxymethyl cellulose grafted with acrylic acid-acrylamide, was adjusted in Comparative Example 4 and Comparative Example 5 compared with Example 1, wherein the amount of carboxymethyl cellulose grafted with acrylic acid-acrylamide was reduced in Comparative Example 4, the number of polar groups in the system decreased, the crosslinking performance of the gel patch decreased, and the lack of the filler, the formability of the gel patch decreased, the release of the active ingredient was slow, and the performance decreased significantly; the excessive amount of filler added in Comparative Example 5 would lead to excessive crosslinking, and the active ingredient was difficult to penetrate.

[0121] Combining Example 1 and Comparative Example 6, it can be seen that the initial adhesion, adhesion and average cumulative permeability of the gel patch obtained in Comparative Example 6 are lower than those in Example 1, indicating that the adhesion performance and transdermal permeability of Comparative Example 6 are lower than those of Example 1. The reason may be that the filler carboxymethyl cellulose used in Comparative Example 6 is not grafted with acrylic acid, the content of polar groups is reduced, and the binding force between the filler carboxymethyl cellulose and the skeleton material is reduced, and the dispersibility in the system is reduced, which leads to the performance of the gel patch being reduced.

[0122] Combining Example 1 and Comparative Example 7, it can be seen that the initial adhesion, adhesion and average cumulative permeability of the gel patch obtained in Comparative Example 7 are lower than those in Example 1, indicating that the adhesion performance and transdermal permeability of Comparative Example 7 are lower than those in Example 1. The reason may be that inorganic fillers are used in Comparative Example 7. First, compared with carboxymethyl cellulose grafted with acrylic acid-acrylamide, the inorganic fillers contain lower polar groups and are more likely to agglomerate in the system, resulting in reduced crosslinking performance and affecting the performance of the gel patch. Secondly, compared with inorganic fillers, carboxymethyl cellulose grafted with acrylic acid-acrylamide has soft molecular chains, which is conducive to mutual combination with the skeleton material. It can accommodate the active ingredients and improve the permeability of the active ingredients. The crosslinking structure and the polar groups contained are conducive to the increase of the adhesion of the gel patch.

[0123] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A gel patch for external use of non-steroidal anti-inflammatory drugs, comprising a backing layer, a paste layer and an anti-adhesive layer, characterized in that: The paste layer includes the following raw materials by mass fraction: Active ingredient 0.3-5%; Skeleton material 3-15%; Filler 0.5-10%; Cross-linking agent 0.03~1%; Cross-linking regulator 0.05~5%; Moisturizer 5-20%; Penetration enhancer 0.2-5%; Thickener 0.5~5%; pH adjuster 0.2-2%; Purified water balance; The filler is carboxymethyl cellulose grafted with acrylic acid-acrylamide; The raw materials of the carboxymethyl cellulose grafted with acrylic acid-acrylamide include carboxymethyl cellulose, acrylic acid and acrylamide in a mass ratio of 1:(3-4):(3-4); The skeleton material is polyacrylic acid-polysiloxane; the raw materials of the polyacrylic acid-polysiloxane include acrylic acid and methacryloyloxypropyl cage-type polysilsesquioxane in a mass ratio of 1: (0.04-0.07).

2. The gel patch of external nonsteroidal anti-inflammatory drugs according to claim 1, characterized in that: The carboxymethyl cellulose grafted with acrylic acid-acrylamide is prepared according to the following method: In a nitrogen atmosphere, carboxymethyl cellulose is added to distilled water, the temperature is increased to 50-60°C, and the carboxymethyl cellulose aqueous solution is obtained by stirring and dissolving; a neutralizer is added to acrylic acid, the pH value is adjusted to 6.5-7, and then the neutralized acrylic acid, acrylamide and a cross-linking agent are added to the carboxymethyl cellulose aqueous solution, and the mixture is stirred and mixed for 10-15 minutes, and then an initiator is added, the temperature is increased to 40-45°C, and the reaction is stirred for 3-3.5 hours, and then the carboxymethyl cellulose grafted with acrylic acid-acrylamide is obtained through washing and drying.

3. The gel patch of external nonsteroidal anti-inflammatory drugs according to claim 2, characterized in that: The cross-linking agent is N,N-methylenebisacrylamide, and the mass ratio of the cross-linking agent to carboxymethyl cellulose is (0.006-0.008):1; the initiator is one or a combination of ammonium persulfate and ammonium bisulfite, and the mass ratio of the initiator to carboxymethyl cellulose is (0.06-0.15):

1.

4. The gel patch of external nonsteroidal anti-inflammatory drugs according to claim 1, characterized in that: The polyacrylic acid-polysiloxane is prepared according to the following method: Azobisisobutyronitrile and methacryloyloxypropyl cage-type polysilsesquioxane are added to a solvent, and acrylic acid is added after mixing. In a nitrogen atmosphere, the temperature is increased to 60-65° C., and the mixture is stirred for reaction for 5-6 hours, and then washed and dried to obtain polyacrylic acid-polysiloxane.

5. The gel patch of external nonsteroidal anti-inflammatory drugs according to claim 1, characterized in that: The active ingredient comprises one or a combination of diclofenac, ibuprofen, ketoprofen, flurbiprofen, indomethacin, piroxicam and loxoprofen.

6. The gel patch of external nonsteroidal anti-inflammatory drugs according to claim 1, characterized in that: The penetration enhancer includes one or a combination of laurocapram, menthol, isopropyl myristate, peppermint oil, oleic acid, propylene glycol, and polyethylene glycol.

7. The gel patch of external nonsteroidal anti-inflammatory drugs according to claim 1, characterized in that: The cross-linking agent includes one or a combination of aluminum hydroxide, aluminum glycolate, aluminum sulfate, composite aluminum salt, aluminum chloride, and aluminum citrate; The cross-linking regulator includes one or a combination of tartaric acid, citric acid, malic acid, edetic acid and sodium salts thereof; The moisturizer includes one or a combination of glycerin, propylene glycol, sorbitol, and polyethylene glycol; The viscosity enhancer includes one or a combination of gelatin, gum arabic, tragacanth gum, peach gum, xanthan gum, and guar gum; The pH adjuster includes one or a combination of L-tartaric acid, DL-tartaric acid, phosphoric acid, citric acid, and malic acid.

8. A method for preparing a gel patch of a topical nonsteroidal anti-inflammatory drug according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: S1. The active ingredient, the penetration enhancer and the viscosity enhancer are mixed to obtain a first mixed solution; S2. The filler and the skeleton material are mixed and added to purified water, and stirred to obtain a second mixed solution; S3. The cross-linking agent, the cross-linking regulator and the pH regulator are added to the humectant, and the mixture is stirred and dispersed to obtain a third mixed solution; S4. The first mixed liquid, the second mixed liquid and the third mixed liquid are stirred and mixed to form a uniform white paste, which is then coated on the backing layer, covered with an anti-adhesive layer and pressed, and finally cut to obtain a gel patch of external non-steroidal anti-inflammatory drugs.